2019
DOI: 10.1186/s13690-019-0349-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a health education intervention on hypertension-related knowledge, prevention and self-care practices in Nigerian retirees: a quasi-experimental study

Abstract: Background Education is vital to increasing knowledge, improving prevention and self-care practices for hypertension in older adults. This study aimed to determine the effectiveness of a health education intervention in improving hypertension (HT) knowledge, prevention and self-care practices among retirees in Enugu State, South-east, Nigeria. Methods In this quasi-experimental study, we enrolled 400 participants in Enugu and Nsukka cities in Enugu State, south-east Nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 68 publications
3
31
0
2
Order By: Relevance
“…For instance, one meta-analysis of 13 studies conducted in middle-income countries showed that group education and other supportive methods improved the adherence to lifestyle modification [ 28 ]. Similarly, another study revealed group counselling and home visits encourage the participants to adopt healthy self-care practices [ 29 ]. Therefore, health education is a tool to improve patient engagement and to begin and maintain adherence to lifestyle modification and compliance with medications [ 30 ] which is ultimately one of the strongest tools for the prevention of cardiovascular disease [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one meta-analysis of 13 studies conducted in middle-income countries showed that group education and other supportive methods improved the adherence to lifestyle modification [ 28 ]. Similarly, another study revealed group counselling and home visits encourage the participants to adopt healthy self-care practices [ 29 ]. Therefore, health education is a tool to improve patient engagement and to begin and maintain adherence to lifestyle modification and compliance with medications [ 30 ] which is ultimately one of the strongest tools for the prevention of cardiovascular disease [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the level of knowledge after an average intervention was able to answer some of the indicators include a definition of hypertension, treatment of hypertension, treatment adherence, lifestyle, healthy diet and complications that are suffered by people with hypertension. Ozoemena et al 26…”
Section: Discussionmentioning
confidence: 99%
“…Ozoemena et al. 26 explain give health education interventions hypertension increase knowledge includes a healthy diet, medication adherence, prevention and treatment practices hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is a major risk factor for cardiovascular disease and a cause of premature death globally [1]. The prevalence of hypertension is projected to increase to 29.2% in 2025 [2].…”
Section: Introductionmentioning
confidence: 99%